Disruptive seeds and transformation pathways for Guatemala's food system - Rutting, Lucas; Veeger, Marieke; Breymann F. Randolph von (CGIAR Initiative on Climate Resilience, 2023)
This presentation summarizes the Disruptive Seeds approach to transformative change and briefly explains how it is applied in the context of ClimBeR’s Policy Pathways research (Work Package 3) in Guatemala. It also describes the progress of the project thus far, the planning for 2023, and highlights a few promising seed initiatives (i.e., sustainable, bottom-up initiatives that can contribute to transformative change).